"Lifestyle, finitude, or inequality?": Illness explanation in Kathlyn Conway's and Arthur Frank's cancer memoirs. (September 2022) - Huang, Hwa-Yen
The lifestyle model, which attributes etiological power and moral responsibility to the individual, is dominant in health promotion discourse. While sociologists rightly critique this model's individualistic outlook, there has been insufficient distinction between the two anti-individualistic models that commonly inform their work: the well-known "sociological model" and the culturally influential but under-conceptualized model tentatively called the "finitude model." Not only is there insufficient awareness of the different etiological causes (inequality and human fragility) and political orientations (redistribution and recognition) underlying the sociological and finitude models, but there is also insufficient recognition of how the finitude model may inform illness explanation. To raise awareness about the existence and analytical utility of the finitude model, I elucidate its core assumptions through a brief review of some influential texts in late-modern health politics. Further, I illustrate the empirical utility of the notion of the finitude model by analyzing how it is used to explain illness in Arthur Frank's and Kathlyn Conway's influential cancer memoirs. Thematic analysis of the memoirs produces two major findings. First, Frank and Conway rely on the finitude model to claim victimhood and blame the blamers. Second, they seem unaware of the double-edged character of such a model, which tends to downplay how social inequality shapes health. My analysis reveals the one-sidedness of both the finitude and sociological models, and that any illness explanation therefore needs to integrate both anti-individualistic models to challenge the lifestyle model successfully.